Interest on reserves and the flexibility of monetary policy in the euro area - Ulrike Neyer (Research On Money in the Economy (ROME), 2007)
This paper shows that remunerating required reserves can increase the flexibility of monetary policy. The remuneration at the current repo rate implies constant net marginal interest costs of holding required reserves. This allows the central bank also to change the rate also within a reserve maintenance period without inducing a problematic reserve shifting on behalf of the banks. In the euro area, required reserves are remunerated at an average rate. Therefore, the way in which reserves are remunerated has to be changed in order to make use of the advantage of a higher flexibility of monetary policy.
Keywords: E41; E52; 330; Monetary policy; monetary policy instruments; required reserves; interbank market; Eurosystem